Economic and social outcomes of investment on research and development in Tajikistan’s agrifood system - Khakimov, Parviz; Aragie, Emerta A.; Goibov, Manuchehr; Ashurov, Timur (International Food Policy Research Institute, 2025)
The World Bank’s agriculture sector public expenditure review study (World Bank 2021) findings indicates that public expenditure on agriculture sector remains relatively small at less than one percent of GDP, though grew significantly between 2015 and 2020, and the sector relies heavily on donor financing (54 percent). There is a notable underinvestment in R&D, 0.7 percent of total public expenditure in agriculture sector between 2016-2019, which impacts productivity and climate resilience.